Decriminalization as a Concept of Protection for Narcotics Addicts as Victims - Dijan Widijowati; Bony Daniel (GoAcademica Research & Publishing, 2022)
The criminal law policy that considers every form of dependence caused by narcotics must receive rehabilitation, one of which can be reviewed based on Article 55 of Law Number 35 of 2009 concerning Narcotics. The responsibility of the state to repair and recover addicts from narcotics dependence can be done concretely through jurisprudence that has a paradigm of Protection for narcotics addicts as well as the paradigm of the state which has responsibility for the survival of narcotics addicts against narcotics abusers in Indonesia and how to formulate decriminalization as a form of justice for narcotics addicts. This research is included in normative juridical law research. Legal research that wants to examine the effectiveness of statutory regulation is a comparative study between legal reality and legal ideals, where the law is conceptualized as what is written in legislation or statute is conceptualized as a rule or norm, which is a benchmark for human behaviour that is considered appropriate. The study results show that the laws and regulations governing narcotics require renewal of the substance of the articles in the direction that describe the qualifications of addicts as victims or addicts as perpetrators of narcotics crimes; the law can substantively determine concrete Protection for drug addicts.